Functional Characterization of Rare Variants in the SHOX2 Gene Identified in Sinus Node Dysfunction and Atrial Fibrillation - Hoffmann, Sandra; Paone, Christoph; Sumer, Simon A.; Diebold, Sabrina; Weiss, Birgit; Roeth, Ralph; Clauss, Sebastian; Klier, Ina; Kääb, Stefan; Schulz, Andreas; Wild, Philipp S.; Ghrib, Adil; et al. (Frontiers in Genetics, 2019)
Sinus node dysfunction (SND) and atrial fibrillation (AF) often coexist, however the molecular mechanisms linking both conditions remain elusive. Mutations in the SHOX2 gene have been recently associated with early-onset and familial AF. Shox2 is a key regulator of sinus node development, and its deficiency leads to bradycardia, as demonstrated in animal models. To provide an extended SHOX2 gene analysis in patients with distinct arrhythmias, we investigated SHOX2 as a susceptibility gene for SND and AF by screening 98 SND patients and 450 individuals with AF. The functional relevance of the novel mutations was investigated in vivo and in vitro, together with the previously reported p.H283Q variant. A heterozygous missense mutation (p.P33R) was identified in the SND cohort and four heterozygous variants (p.G77D, p.L129=, p.L130F, p.A293=) in the AF cohort. Overexpression of the pathogenic predicted mutations in zebrafish revealed pericardial edema for p.G77D and p.H283Q, whereas the p.P33R and p.A293= variants showed no effect. In addition, a dominant-negative effect with reduced heart rates was detected for p.G77D and p.H283Q. Reporter assays demonstrated for both missense variants p.P33R and p.G77D significantly impaired transactivation activity, similar to the described p.H283Q variant. Also, a reduced Bmp4 target gene expression was revealed in zebrafish hearts upon overexpression of the p.P33R mutant. This study associates additional rare variants in the SHOX2 gene implicated in the susceptibility to distinct arrhythmias and allows frequency estimations in the AF cohort (3/990). We also demonstrate for the first time a genetic link between SND and AF involving SHOX2.